2019
DOI: 10.21873/invivo.11593
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surgical Procedures that Affect the Hemodynamics Using the FloTrac System in Esophageal Cancer Patients

Abstract: Background/Aim: Esophagectomy is more invasive compared to other gastrointestinal surgery types. Perioperative circulatory management is important to avoid postoperative heart complications. The FloTrac sensor along with the Vigileo monitor is a minimally invasive haemodynamic monitoring device. Here, we examined different surgical procedures affecting hemodynamics using the FloTrac system in esophageal cancer patients following esophagectomy. Patients and Methods: Thirty-one patients undergoing postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…The advantage of this option is that highly valuable information can easily be obtained by the system, which is directly connected to the arterial pressure waveform. We previously reported surgical procedures that affect the hemodynamics using the FloTrac system in patients with esophageal cancer following esophagectomy (9). As a result, we demonstrated that the retrosternal route potentially influences the haemodynamic stability measured by the FloTrac / Vigileo system (9).…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…The advantage of this option is that highly valuable information can easily be obtained by the system, which is directly connected to the arterial pressure waveform. We previously reported surgical procedures that affect the hemodynamics using the FloTrac system in patients with esophageal cancer following esophagectomy (9). As a result, we demonstrated that the retrosternal route potentially influences the haemodynamic stability measured by the FloTrac / Vigileo system (9).…”
Section: Introductionmentioning
confidence: 80%
“…In addition, these results reflect that T4 cases of cancer which were judged during operation, retrosternal route significantly had been selected for getting surgery compared with other routes in this study. We previously reported the retrosternal route potentially influences the haemodynamic stability (CI or SVV) measured by the FloTrac / Vigileo system (9). We routinely select postmediastinal route in patients with esophageal cancer and R0 resection in recent year.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations